The Effect of Information Sources and Communication Channels on the diffusion of Innovation in a Data Base Development Environment - Nilakanta, Sree; Scamell, Richard W. (Management Science, 1990)
Increasing importance of emerging information technology, especially the data base component, has prompted the examination of the process of diffusion of innovations in the context of data base system development. This paper (1) examines the extent to which information sources and communication channels facilitate the diffusion of data base design tools and techniques, (2) studies how different information sources and communication channels influence diffusion and (3) assesses whether data base design tools and techniques applicable to the different stages of system development are diffused at different rates. In facilitating the diffusion of data base design tools and techniques, organizational resources such as information sources, communication channels and a technical support function are found to influence only certain classes of these innovations.